COMPARATIVE STUDY: CORRELATION OF UREA AND SERUM CREATININE WITH DURATION OF DIABETES AND GLYCEMIC INDEX IN INDIVIDUALS WITH TYPE 1 AND 2 DIABETES MELLITUS. - Prashant Kumar; Akhilesh Kumar; Rahul Raj (Student's Journal of Health Research, 2023)
Background:  Kidney failure and nephropathy, defined as a dysfunctional kidney with a decline in ultrafiltration and a rise in blood urea and creatinine levels, are frequently caused by diabetes. Aim: The motive of this research was to evaluate the concentration of blood urea and creatinine in individuals with diabetes, and also to examine the relationship between these parameters and the duration of diabetes as well as glycosylated hemoglobin concentration. Methods:  Concentrations of urea and creatinine in the blood were evaluated in samples of Juvenile diabetes and Diabetes mellitus patients attending diabetic clinics as well as non-diabetic patients in a tertiary hospital. For the study, 144 male participants between the ages of 35 and 55 were chosen for each group. All trial participants' fasting blood sugar, post-meal blood sugar parameters, and glycosylated hemoglobin were ascertained. The relationship between blood creatinine and urea levels, glycosylated hemoglobin, and length of illness in all diabetes participants was examined. Results:  In the type 1 study group, blood creatinine and urea levels were correlated with glycosylated hemoglobin levels and the length of diabetes, but not with the Diabetes mellitus study group. Serum creatinine (F-value = 50.96) and urea (F-value = 33.4) levels increased statistically significantly in the diabetes groups relative to the control group. Conclusion:  Creatinine and urea are straightforward and practical indicators that can be used as predictive assays to evaluate the condition of the kidneys (nephropathy) in individuals with diabetes. Recommendations: Intensive treatment can address elevated HbA1c levels in diabetes, but it may not reverse rising serum urea and creatinine caused by permanent kidney damage. Early detection and intervention are crucial to control glomerular injury and prevent further increases in serum urea and creatinine levels.